STRENGTHENING NETWORK LEARNING DURING THE COVID-19 PANDEMIC - Ellisa Fitri Tanjung; Mavianti Mavianti (Proceeding International Seminar of Islamic Studies, 2022)
In order to narrow the spread of Covid-19, the Indonesian government has made a policy by implementing social distancing at every level of society, including learning activities at the elementary and secondary school levels. This policy certainly has an impact on education in Indonesia, especially on the learning process in schools. Schools were closed but learning activities continued by switching to online learning. This policy certainly has an impact on education in Indonesia, especially on the learning process in schools. Schools were closed but learning activities continued by switching to online learning. some of the obstacles faced, namely not all schools find a way out and immediately take action to maximize the online teaching and learning process. Data was collected using the methods of observation, interviews and documentation. Data analysis was carried out by examining all data collected from observations, interviews and documentation. The conclusions from this study are: The strategy created by the teacher in maximizing Islamic Religious Education learning during the covid 19 pandemic is the most effective way to increase student interest in learning and maximize the learning process by using available media, more effective and more enjoyable.Keywords: Learning Strategy, Covid 19, Islamic Religious Education.